Two-dimensional finite element analysis of steel-secondary linear induction motor under variable frequency and loading conditions - Kurum, Hasan; Shobair, Ahmed I.A (My University, 2001)
Short-primary sheet-secondary type linear induction motors (LIM) have been proposed for a number of applications [1] including high speed ground transportation [2-3]. In the literature, steady state performance characteristics of LIM have been determined using one, two and three-dimensional field analysis [4-7]. Furthermore, it has been shown that for steady-state analysis, a quasi-one-dimensional approach, which accounts for the three mentioned effects by superposition is adequate for practical reasons [8]. In this paper a doubled-sided linear induction motors (DLIM) with a steel-sheet secondary, which is generally used in high-speed ground transportation, is modeled. The model is obtained from the field analysis using finite elements in x-y plane. All fields are then assumed to be invariant in the z-direction with current restricted to the z-direction. Saturation in the stator is taken into account. The solution is found by iteration and adjustment of ? for the elements until ?, B and H coincide on the B-H curve. Thrust force is predicted. The flux pattern for a 4-pole machine is drawn. Computational results are verified by experimental measurements under variable frequency and loading conditions. In fact the analysis can be extended to three dimensional finite element modeling following the method outlined below.
Dvodimenzionalna analiza ?eli?nog sekundarnog linearnog indukcijskog motora metodom kona?nih elemenata pod promjenjivom frekvencijom i optere?enjem
Keywords: Finite element method; Linear induction motor; Steel-sheet secondary; Thrust force; Variable frequency excitation